Zapinki tarczowate z motywem krzyża z Tumian, pow. Olsztyn - Grzegorczyk, Andrzej (Acta Universitatis Lodziensis. Folia Archaeologica, 2017)
Olsztyn Group has been formed in the later phase of the Migration Period (Phase E), developed in Masurian Lake District. This group had maintained lots of contacts with southern and western areas of Europe which can be proof, by the found goods of external origin. At the end-stage of Olsztyn Group (7th) round brooches with various ornament become popular. One of them was the brooches ornamented with the cross. Made of bronze and silver has in central part placed filigree cross or its imitation. These items are unique because that kind of ornament had been used in the western part of Europe in the area of upper Rhine. Popular among Franks, Alamans and Turings because dissemination of Christian religion. Strong believes about protective function of cross had been reason of placing it at ceramic and weapon by cultures of western Europe. The same symbol or its imitation had been used by culture at Mazurian Lakelands due the lack of union this kind of symbol with the local lands. Round brooches from Tumiany cannot be connected with influence of Christian mission. There is no evidence to support such a claim. Most likely, brooches with cross ornament had been used by citizens of Mazury as typical jewelry without connection with it religious meaning. But these artifacts may indicate extensive contacts with western Europe and earliest contacts with Christianity, in this part of the continent.